Serum B-cell activating factor and lung ultrasound B-lines in connective tissue disease related interstitial lung disease - Wang, Yukai; Xie, Xuezhen; Zheng, Shaoyu; Du, Guangzhou; Chen, Shaoqi; Zhang, Weijin; Zhuang, Jinghua; Lin, Jianqun; Hu, Shijian; Zheng, Kedi; Mikish, Angelina; Xu, Zhuangyong; et al. (Frontiers in Medicine, 2022)
Objective To investigate the role of serum B-cell activating factor (BAFF) and lung ultrasound (LUS) B-lines in connective tissue disease related interstitial lung disease (CTD-ILD), and their association with different ILD patterns on high resolution computed tomography (HRCT) of chest. Methods We measured the levels of BAFF and KL-6 by ELISA in the sera of 63 CTD-ILD patients [26 with fibrotic ILD (F-ILD), 37 with non-fibrotic ILD (NF-ILD)], 30 CTD patients without ILD, and 26 healthy controls. All patients underwent chest HRCT and LUS examination. Results Serum BAFF levels were significantly higher in CTD patients compared to healthy subjects (617.6 ± 288.1 pg/ml vs. 269.0 ± 60.4 pg/ml, p < 0.01). BAFF concentrations were significantly different between ILD group and non-ILD group (698.3 ± 627.4 pg/ml vs. 448.3 ± 188.6 pg/ml, p < 0.01). In patients with ILD, BAFF concentrations were significantly correlated with B-lines number (r = 0.37, 95% CI 0.13–0.56, p < 0.01), KL-6 level (r = 0.26, 95% CI 0.01–0.48, p < 0.05), and Warrick score (r = 0.33, 95% CI 0.09–0.53, p < 0.01), although all correlations were only low to moderate. B-lines number correlated with Warrick score (r = 0.65, 95% CI 0.48–0.78, p < 0.01), and KL-6 levels (r = 0.43, 95% CI 0.21–0.61, p < 0.01). Patients with F-ILD had higher serum BAFF concentrations (957.5 ± 811.0 pg/ml vs. 516.1 ± 357.5 pg/ml, p < 0.05), KL-6 levels (750.7 ± 759.0 U/ml vs. 432.5 ± 277.5 U/ml, p < 0.05), B-lines numbers (174.1 ± 82 vs. 52.3 ± 57.5, p < 0.01), and Warrick score (19.9 ± 4.6 vs. 13.6 ± 3.4, p < 0.01) vs. NF-ILD patients. The best cut-off values to separate F-ILD from NF-ILD using ROC curves were 408 pg/ml for BAFF (AUC = 0.73, p < 0.01), 367 U/ml for KL-6 (AUC = 0.72, p < 0.05), 122 for B-lines number (AUC = 0.89, p < 0.01), and 14 for Warrick score (AUC = 0.87, p < 0.01) respectively. Conclusion Serum BAFF levels and LUS B-lines number could be useful supportive biomarkers for detecting and evaluating the severity and/or subsets of CTD-ILD. If corroborated, combining imaging, serological, and sonographic biomarkers might be beneficial and comprehensive in management of CTD-ILD.